Suchmaschinen unter der Lupe: Informationsherrschaft und ihre Schranken - Martin Peitz; Heike Schweitzer (Wirtschaftsdienst, 2016)
Suchmaschinen ermöglichen Nutzern einen schnellen Zugang zu Informationen, die sie konkret suchen oder dort erst entdecken. Sie haben sich zu wichtigen Informationsintermediären entwickelt. In der breit geführten Debatte über eine mögliche Regulierung von Suchmaschinen sprechen sich die Autoren gegen eine Ex-ante-Regulierung aus. Das Wettbewerbsrecht reiche aus, um vor marktbezogenen Formen des Missbrauchs von 'Informationsmacht' zu schützen. Es sollte aber über neue Methoden zur Ermittlung des Missbrauchs von Marktmacht nachgedacht werden. Die regulierende Funktion, die Suchmaschinen mit Blick auf den Schutz des Allgemeinen Persönlichkeitsrechts auf ihrer Plattform wahrzunehmen haben, rechtfertigt es aus Sicht der Autoren nicht, Suchmaschinen zu einem neuen 'regulierten Sektor' zu erklären. – – Informational Power and Its Limits : Informational power by search engines should be analysed from different perspectives. On the one hand, unlimited access to personal data can be in conflict with the interests of individuals whose data can be accessed. These interests are part of a right to privacy, including a 'right to be forgotten,' which, however, must be balanced against the public interest in disclosure of information. Balancing these conflicting interests is a difficult task - a task that lies with the search engines themselves. On the other hand, firms and individuals may have an interest in their information to be found, in particular (but not only) for commercial purposes. Suppressing or 'downgrading' this information as displayed to users may significantly reduce visibility. In light of these interests, it has been proposed to oblige search engines to implement 'search neutrality'; i.e., that they have to present search results in an unbiased way. In this article, we take a clear position against exante regulation. Instead, competition law provides a sufficient framework, to protect against the abuse of 'informational' market power. We sketch a new approach that may allow competition law to be applied more quickly in dynamic markets such as internet search markets.
Keywords: K20; K21; L40; 330